Complete mitochondrial genome of Triplophysa bleekeri (Cypriniformes: Balitoridae: Nemacheilinae), and analysis of mitochondrial genetic variability among Triplophysa species. (1st November 2016) - Li, Jiuxuan; Yang, Kun; Si, Shengjuan; Zhang, Xiuyue; Song, Zhaobin
Abstract: The complete mitochondrial genome of the stone loach Triplophysa bleekeri collected from the Anning River, a tributary of the Yalong River, in Sichuan Province was sequenced. The genome is 16, 573 bp in length, consisting of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a noncoding control region. Most of the genes are encoded on the heavy strand, except for ND6 and eight tRNAs. The overall base composition of T. bleekeri is 28.1% for A, 28.4% for T, 25.5% for C, 18.0% for G, with a slight A+T bias of 56.5%. The complete mitochondrial genetic variability is high among different Triplophysa species and between the two T. bleekeri individuals from different rivers.